Where the violence happened matters. Geopolitical framing and assessments of collective responsibility for historical violence. (March 2021) - Mazur, Lucas B.
Abstract: Mass violence always takes place in a particular geopolitical context, and how that context is understood influences perceptions of collective responsibility. As international borders shift, often in the wake of war, events that occurred within one geopolitical entity can be understood has having taken place in another. The influence of such geopolitical framing on judgments of collective responsibility remains understudied. Two studies examine how geopolitical frames lead to shifting assessments of collective responsibility for historical mass violence. By depicting historical violence within a particular geopolitical entity (e.g., a country), that entity was perceived as being more responsible for the violence. The studies are set within the contexts of German-occupied Poland and the British occupation of the Indian subcontinent. The ramifications of these findings are discussed for the teaching of history, the commemoration of historical victimhood, and for our understanding of assessments of collective responsibility and geopolitical framing more broadly.